Plantarisin Asal Lactobacillus plantarum IIA-1A5 sebagai Pengawet Alami Daging Ayam Bagian Paha pada Suhu Refrigerator - Siswara, H. N.; Arief, I. I.; Wulandari, Z. (Jurnal Ilmu Produksi dan Teknologi Hasil Peternakan, 2019)
Naturally preservative has potential to appllied as food preservative. A biopreservative can used for food is bacteriocin. Bacteriocin is peptide compound produced by lactic acid bacteria and has antimicrobial activity. Lactobacillus plantarum is one of lactic acid bacteria produce bacteriocin called plantaricin. Plantaricin has antimicrobial activity against pathogen bacteria. Aplication of plantaricin will become an alternative for developing biotechnology in biopreservative. The aim of this research was to evaluate the effectiveness of plantaricin IIA-1A5 as biopreservative to physical properties and microbiological chicken meat at refrigerator temperature. There were two methods used, purification of plantaricin and its aplication to chicken meat. This research used completely randomized design with factorial pattern, then Duncan Multiple Rank Test. The results showed that there was a significant (P<0.05) interaction of gived plantarisin with specific storage time (0, 2, 4, 6, 8, and 10 days) in chicken meat on the quality of meat. As conclusion, plantaricin IIA-1A5 effectively inhibited pathogenic bacteria so total microbe was lower than control. Plantaricin could be recommended as a biopreservative for chicken meat.